Ethnobotanical Studies of North–East Region from Nashik District (Maharashtra, India) - Wagh, A N; Pawar, N B (Plantae Scientia, 2021)
The present paper deals with 41 ethnobotanical plants with their common names belonging to 18 families from North-East region of Nashik district. The plants were used by local people for food, fodder, medicine, religious ceremonies. The information was gathered from Vaidu, Bhagat, Local peoples, Shepherds. The families like Fabaceae, Euphorbiaceae, Apocynaceae, Combretaceae, Apiaceae, Pteridaceae are dominant families for use as ethnobotanical species.